Experimental Investigation of Pull and Energy Characteristics of Generator Drive Unit to Be Used with Container Flats” Three-Piece Bogies - V. G. Kargin; S. N. Naumenko; V. V. Burov; I. N. Chuvashov; S. L. Samoshkin (Вестник Научно-исследовательского института железнодорожного транспорта, 2015)
To adapt container flats for transportation of high-capacity reefers (HCR) there was developed stand-alone power supply system (SAPSS) to be mounted on the flatcar three-piece freight bogie. Such a system ensures power supply to HCR all over the travel route by rail. One of the SAPSS key components proves to be generator drive unit comprising generator, V-belt transmission and single-reduction gear unit with dissectible driving gear mounted in the midpart of the wheelset axle. To confirm workability of the generator drive unit and obtain its pull and energy characteristics there were conducted rig tests of its prototype using for this purpose exerciser developed by the VNIIZhT design center. The exerciser was equipped with instrumentation systems capable to determine V-belt tension by the tension screw force value and assess slipping by rotating speeds of the driving and driven V-belt pulleys. Rig tests implied container flat running at various speeds. Three SAPSS loading modes were tested inclusive of open circuit operation. There was purposely developed testing procedure, allowing to assess slipping of the V-belt transmission within the accuracy of 0.01 %. Experimental data were collated with calculation results obtained by the authors beforehand. The SAPSS prototype tests outcomes evidence that generator drive unit is capable to support the system operation at power levels up to 16±1 kW within the container flat running speed range from 30 to 132 kph.